2010
DOI: 10.1111/j.1442-1984.2010.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of different sites of self-incompatibility reaction in four Anathallis (Orchidaceae, Pleurothallidinae) species

Abstract: Orchids are typically self-compatible, and in this family self-fertilization is usually prevented by pre-pollination barriers. However, genetic self-incompatibility has been found in species of some lineages of the myophilous subtribe Pleurothallidinae. We carried out experimental pollinations to determine the mating systems of four Anathallis species, a representative genus of a large clade of this subtribe. This is one of the few clades of Pleurothallidinae not studied on this subject to date. All four speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
(35 reference statements)
0
12
0
1
Order By: Relevance
“…Pollen tube growth stopped at different positions in the style or ovary, which is consistent with previous reports in other orchids. For example, pollen tube growth stopped at certain style positions in P. adamantinensis and P. fabiobarrosii , while it stopped at the ovary in Restrepia species, and the pollinia did not germinate in M. infracta , Octomeria , Stelis , and Specklinia [ 2 , 23 , 26 , 27 ]. This suggests that there are a variety of SI determinants in the Orchidaceae, even in Dendrobium .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen tube growth stopped at different positions in the style or ovary, which is consistent with previous reports in other orchids. For example, pollen tube growth stopped at certain style positions in P. adamantinensis and P. fabiobarrosii , while it stopped at the ovary in Restrepia species, and the pollinia did not germinate in M. infracta , Octomeria , Stelis , and Specklinia [ 2 , 23 , 26 , 27 ]. This suggests that there are a variety of SI determinants in the Orchidaceae, even in Dendrobium .…”
Section: Discussionmentioning
confidence: 99%
“…In some species, such as Masdevallia infracta , Octomeria , Stelis , Specklinia , and Anathallis spp. (except A. microphyta ), pollen after pollination does not germinate [ 26 ], and self-pollination of 26 species of Restrepia (Orchidaceae) revealed that pollen tubes grow only into the top third of the ovary [ 23 ], while Pleurothallis adamantinensis and P. fabiobarrosii are strictly self-incompatible because pollen tube growth ceases near the base of the style [ 27 ]. We identified two SI species in Dendrobium : Dendrobium longicornu and D. chrysanthum .…”
Section: Introductionmentioning
confidence: 99%
“…Such a pattern is also reported from other species, e.g. Chamaecrista keyensis (Liu, Koptur 2003), Impatiens reptans (Tian et al 2004), Dianthus guliae (Gargano et al 2009), Pultenaea villosa (Ogilvie et al 2009) and Anathallis species (Gontijo et al 2010).…”
Section: Resultsmentioning
confidence: 63%
“…this subtribe, cladistic analysis has identifi ed eight main clades (designated A to H), ( Pridgeon and Chase, 2001 ). Other studies have revealed the existence of SI systems operating within seven of the eight clades, with many suggesting a link between SI and myophily ( Christensen, 1992 ;Borba et al, 2002 ;Blanco and Barbosa, 2005 ;Tremblay and Ackerman, 2007 ;Barbosa et al, 2009 ;Gontijo et al, 2010 ;Borba et al, 2011 ). The remaining clade (clade B), which includes the Pleurothallid genus Restrepia , is the only one in which the operation of SI has yet to be confi rmed.…”
mentioning
confidence: 97%
“…Although studied in many angiosperm families, SI is often considered relatively rare in the Orchidaceae, with most species being self-compatible and "avoiding" self-pollination by other means ( Agnew, 1986 ;Dressler, 1990Dressler, , 1993Borba and Semir, 1999 ;Singer and Cocucci, 1999 ;Borba et al, 2001 ;Ingrouille and Eddie, 2006 ;Roberts, 2003 ;Gontijo et al, 2010 ). Dressler (1990Dressler ( , 1993 ) estimated SI to occur in 10% of orchid species, but considered its full extent still to be established ( Dressler, 1993 ).…”
mentioning
confidence: 99%